Neuroprotective Effects of the Inert Gas Argon on Experimental Traumatic Brain Injury In Vivo with the Controlled Cortical Impact Model in Mice - Fritz I. Schneider; Sandro M. Krieg; Ute Lindauer; Michael Stoffel; Yu-Mi Ryang (Biology, 2022)
Argon has shown neuroprotective effects after traumatic brain injury (TBI) and cerebral ischemia in vitro and in focal cerebral ischemia in vivo. The purpose of this study is to show whether argon beneficially impacts brain contusion volume (BCV) as the primary outcome parameter, as well as secondary outcome parameters, such as brain edema, intracranial pressure (ICP), neurological outcome, and cerebral blood flow (CBF) in an in-vivo model. Subjects were randomly assigned to either argon treatment or room air. After applying controlled cortical impact (CCI) onto the dura with 8 m/s (displacement 1 mm, impact duration 150 ms), treatment was administered by a recovery chamber with 25%, 50%, or 75% argon and the rest being oxygen for 4 h after trauma. Two control groups received room air for 15 min and 24 h, respectively. Neurological testing and ICP measurements were performed 24 h after trauma, and brains were removed to measure secondary brain damage. The primary outcome parameter, BCV, and the secondary outcome parameter, brain edema, were not significantly reduced by argon treatment at any concentration. There was a highly significant decrease in ICP at 50% argon (p = 0.001), and significant neurological improvement (beamwalk missteps) at 25% and 50% argon (p = 0.01; p = 0.049 respectively) compared to control.